Testing the Relationship Between Government Spending and Revenue : Evidence From GCC Countries - Wang, Qing (IMF Working Papers; Working Paper ;, 2002)
The paper examines the direction of causality between total government expenditure and revenue in oil-dependent GCC countries by utilizing a cointegration and error-correction modeling framework, and by calculating a variance decomposition analysis. In addition, it presents impulse responses to shed light on the dynamic relation of expenditure to a revenue shock. The results confirm expectations that government spending follows oil revenue, suggesting a pro-cyclical expenditure policy to variations in oil revenue. To make budget expenditure less driven by revenue availability, the authorities could resort to a medium-term expenditure framework, so that expenditures can be planned and insulated from volatile short-term revenue availability.